Teaching with and about the Ivory Art from Chukotka and the Bering Strait (Research Note) - Pasternak, Igor (Études Inuit Studies, 2021)
This article relates a pedagogical approach to exploring current directions in the art made with walrus ivory in Chukotka, Russia. Noting the unprecedented and rapidly expanding diversity in the forms and techniques documented over the course of recent ethnographic research, the article outlines a set of ideas and contexts helpful in examining contemporary practices in walrus ivory art. These include a present-day ethnography of the buyer market and its influence on artistic production, a chronology of pertinent developments during the Soviet and post-Soviet periods, and the author’s take, as that of a practicing artist, on differentiating between the formal and conceptual functions of the imagery found in Bering Strait archaeological materials and the recontextualization of this imagery within present-day practices in Chukotka.